Reduced β-lactoglobulin IgE binding upon in vitro digestion as a result of the interaction of the protein with casein glycomacropeptide - Martinez, María Julia (2016)
The aim of this work was to evaluate the effect of the presence of casein glycomacropeptide (CMP) on the in vitro digestibility and potential allergenicity of β-lactoglobulin (β-lg)-CMP mixtures. The digestion products were analyzed by RP-HPLC and RP-HPLC-ESI-MS/MS. The potential allergenicity of the digestion products was studied by human IgE binding by inhibition ELISA with serum samples from children with clinical allergic symptoms to β-lg. No differences were observed by HPLC in the mixtures hydrolysates due to CMP-β-lg interactions. RP-HPLC-ESI-MS/MS results showed different peptides occurring in the mixtures hydrolysates. Additionally, it was observed a significant reduction of β-lg IgE binding in the presence of CMP. The disappearance of epitopes in the digested mixtures could explain the lower IgE binding observed in these systems compared to β-lg. It can be concluded that the presence of CMP in products containing β-lg may modify the digestion products that may reduce the potential allergenicity of β-lg.